Does a ghrelin stimulus during zebrafish embryonic stage modulate its performance on the long-term? - Navarro-Guillén, Carmen (2020)
Metabolic programming refers to the induction, deletion, or impaired development of a somatic structure or "setting" of a physiological system by an early life stimulus operated at a critical period during development. Ghrelin is the only known orexigenic gut hormone, is an acylated peptide that acts as an endogenous ligand specific for growth-hormone secretagogue-receptor. The aim of the present work was to evaluate if an in ovo ghrelin administration could positively influence the zebrafish performance in the long-term and to gain insight on the mechanisms associated to ghrelin regulation of food intake during the larval phase. Food intake, growth potential, protein metabolism, expression of target genes involved in ghrelin, feeding behaviour regulation and locomotor activity were assessed in zebrafish (Danio rerio) larvae at 25 days post-fertilization. Elevated levels of acylated ghrelin in zebrafish eggs did not result in increased growth or food intake. Differences in mRNA expression between larvae fasted for 16 h before and 1 h after feeding were found for igf1ra, gh1 and pomca. Moreover, ghrelin treated larvae showed higher swimming activity, indicating that the peptide may have an important role on foraging activity. The present study addressed for the first time the effects of an early stimulus of ghrelin during the embryonic stage of zebrafish, however, further studies are needed to clarify the metabolic pathways affected by the early stimulus as well as focus on the effects on metabolic regulation of energy balance through lipid and carbohydrate metabolism.